(3GdCMcGe GdLRFjI (B( (3aj GdbQGfGJ hGdeeGRLGJ hGdWdhY hGdZQhH hGdQLYI hGdGSJbGeI (B)s
(3ChdgG (B:s
(3GdHGH GdChd ai bQGfGJ GdchGcH ai GdHQhL GdCKfi YTQ , hgh (B( (3ai (B) (3EKfi YTQ aUdkG GdChd Ydi Mce bQGfGJ RMd dchGcH bQGf RMd hGdeTJQi s
(3BNQgG (B:s
(3hghGA ecI hGdeOjfI hCQV GdYQGb hGdOjde hLHd WHQSJGf GdbeQ dg GdEbdje GdSGHY hEHJOGFg ef MO (B((3eW d(B) (3Edi (B( (3TM (B) (3, hPdc ai GdTeGd hgh GdehUd hBPQHjLGf GdYhGe ef GdfGS ai cd ehVY Je GdcJGH hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS dCHhGH GdcJGHs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs